Exoneration clauses in standard property agreements: between freedom of contract and consumer protection - Junaidi Junaidi (Veteran Law Review, 2026)
Standard agreements are commonly used in property sales to accelerate economic transactions, but they also raise important issues regarding the differing bargaining power of sellers and buyers. A major issue that arises is the use of liability exemption clauses, which protect developers rather than consumers. Taking into account the principles of fairness in contracts and the balance of rights and obligations, this study examines the legitimacy of such clauses in standard property agreements. Furthermore, the study aims to create a model agreement that strikes a balance between contractual freedom and consumer protection. A normative legal study was conducted through legislation, legal concepts, and comparative law. The results indicate that the evaluation of liability exemption clauses must be based on formal legal rules, as well as on substantive justice, transparent communication and balanced risk sharing between the parties involved. To prevent the abuse of standard provisions, the study recommends redesigning property agreements to incorporate fairness testing and consumer protection principles based on risk analysis. By providing a more flexible evaluation framework for common contract practices in the property sector, these findings will contribute to the development of contemporary contract law